Human beta-defensin gene copy number variation and consequences in disease and evolution - Pala, Raquel Rodrigues (2012)
Research on human genetic variation has shown that the human genome is not a fixed, invariant framework, but that there can be extensive structural variation. This variation includes copy number variation (CNV), which can lead to changes in DNA dosage contributing significantly to variation between individual human genomes and heritable traits. Human beta-defensins are small, secreted antimicrobial peptides encoded by DEFB genes located in a cluster of at least seven genes on 8p23.1. These genes are highly variable in copy number but accurate measurement of multiallelic copy number variants is challenging, particularly for high copy numbers, and has not been intensively studied until recently. A new PRT-based (Paralogue Ratio Test) triplex assay was developed to accurately measure the multiallelic beta-defensin copy number variation. The Triplex assay was demonstrated to be an accurate and powerful method to measure copy number variation in large case-control association studies. This method was used to study the beta-defensin CNV in psoriasis disease, showing that high beta-defensin copy number is associated with susceptibility to psoriasis in Caucasians. Studying population variation of CNV showed that variation in copy number of beta-defensin is not significantly different across human populations. To understand the evolutionary history of beta-defensin CNV in the primate lineage, the study of CNV at this locus was carried out in great apes. Beta-densin genes are copy variable in human and chimpanzee, but not in gorilla, suggesting that variation in copy number of beta-defensin genes may have arisen in the human-chimpanzee lineage after the divergence with gorilla.